2004
DOI: 10.1124/dmd.104.001578
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Cyp2c9 and Cyp2c19 in Reconstituted Binary Systems Influence Their Catalytic Activity: Possible Rationale for the Inability of Cyp2c19 to Catalyze Methoxychlor Demethylation in Human Liver Microsomes

Abstract: ABSTRACT:Previous studies in our laboratory showed that among cDNAexpressed human cytochrome P450 (P450) supersomes, CYP2C19 was the most active in methoxychlor-O-demethylation (Hu et al., 2004). However, based on the lack of inhibition of methoxychlor-O-demethylation by monoclonal anti-CYP2C19 antibodies in human liver microsomes (HLM), CYP2C19 did not seem to catalyze that reaction in HLM. By contrast, CYP2C9, much less active than CYP2C19 in supersomes, was the most active in HLM. The current study examines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
56
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 25 publications
(29 reference statements)
1
56
0
Order By: Relevance
“…These complexes could be disrupted by an increase in the ionic strength of the buffer, suggesting that the interactions between the P450s were electrostatic in nature (23,24). Recently, a similar type of interaction also has been reported for CYP2C9 and CYP2C19 in which the activity of CYP2C9 is activated, whereas that of CYP2C19 is inhibited by the presence of the alternate enzyme (25). Thus, it seems that some P450-P450 interactions may have an important role in the regulation of enzyme activity.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…These complexes could be disrupted by an increase in the ionic strength of the buffer, suggesting that the interactions between the P450s were electrostatic in nature (23,24). Recently, a similar type of interaction also has been reported for CYP2C9 and CYP2C19 in which the activity of CYP2C9 is activated, whereas that of CYP2C19 is inhibited by the presence of the alternate enzyme (25). Thus, it seems that some P450-P450 interactions may have an important role in the regulation of enzyme activity.…”
mentioning
confidence: 77%
“…Several studies have shown that the metabolism of numerous substrates by a given P450 enzyme is altered in the presence of other P450s (21,25,(42)(43)(44). The specific interaction with mixed reconstituted systems containing both CYP1A2 and FIGURE 4.…”
Section: Discussionmentioning
confidence: 99%
“…We did not consider the alternate pathways to generate complexes. Like in other studies (19,39), our system was at equilibrium and therefore (29) we could not even in principle determine the path through which these complexes were generated. Our equilibrium binding studies could only reveal which complexes were most likely to be present under reaction conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Our initial titrations and Job plot were limited subsets of data for the system, and thus limited the ability to assess the role of protein-protein interactions in regulating P450 activity. Similarly, reliance on the titration format and small data sets may explain why groups were not able to actually fit data from mixed P450 systems to possible complexation mechanisms (19,32,39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation